Effect of Financial Performance on Company Value With Corporate Social Responsibility as Moderating Variable - Rahmatika Nuuril Imaama; Nur Fadjrih Asyik; Bambang Suryono (Best Journal of Administration and Management, 2022)
This study aims to examine the effect of financial performance as measured by the Current Ratio (CR), Quick Ratio (QR), and Return On Investment (ROI), on firm value (PBV) with Corporate Social Responsibility (CSR) as moderating. This type of research is quantitative research. The sample in this study was obtained using a purposive sampling method, namely the selection of a sampling with certain criteria. Based on the purposive sampling method, 261 samples were obtained from 87 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The analytical method used is multiple linear regression analysis and Moderated Regression Analysis (MRA) Interaction Test with SPSS 25 tool. The results show that: 1) Current Ratio (CR) has a negative effect on firm value, 2) Quick Ratio (QR) has an effect on positive effect on firm value, 3) Return On Investment (ROI) has a positive effect on firm value, 4) Corporate Social Responsibility (CSR) is able to moderate the effect of Current Ratio (CR) on firm value, 5) Corporate Social Responsibility (CSR) is not able to moderate the effect of Quick Ratio (QR) on firm value, 6) Corporate Social Responsibility (CSR) is able to moderate the effect of Return On Investment (ROI) on firm value.